Desain dan Pengembangan Aplikasi Penjualan Berbasis Website di Float Smoothies Shop Medan - Dwi Citra Tarcilia Br Berutu; Abdul Khaliq; Supiyandi (Jurnal Nasional Teknologi Komputer, 2025)
The development of information technology drives digitalization in various sectors, including the culinary business. Medan Float Smoothies Store still uses a conventional sales system, which causes various obstacles in order recording, stock management, and financial reporting. Therefore, this study aims to design and develop a website-based sales system to improve operational efficiency. The research method used is Research and Development (R&D) with the Software Development Life Cycle (SDLC) Waterfall model approach. The results of the study show that the implementation of a PHP and MySQL-based system has succeeded in replacing manual processes, increasing transaction accuracy, and expanding market reach through online ordering features. With this system, customers can easily view products, make transactions, and get stock information in real time. The benefits of this study are increasing business efficiency, reducing transaction errors, and providing a more practical shopping experience for customers.